2018
DOI: 10.1016/j.ijhydene.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Co/Ce loading ratio and reaction conditions on CDRM performance of Co Ce/ZrO2 catalysts

Abstract: This work mainly aims to establish a link between Co/Ce loading ratio in CoeCe/ZrO 2 catalysts and their Carbon Dioxide Reforming of Methane (CDRM) performance. In this context, catalysts with different Co and Ce loadings were prepared and characterized via BET, XRD, HRTEM-EDX, XPS and Raman, and parametrically tested under different CDRM conditions. Dispersion of Co particles was nonhomogeneous on all samples. For the sample with the highest Co/Ce ratio (10%Coe2%Ce/ZrO 2), higher amount of lattice oxygen vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
(57 reference statements)
3
11
0
Order By: Relevance
“…However, Ni-based catalysts tend to become deactivated when subjected to long-term reactions due to C deposition and the sintering of Ni grains. erefore, resistance to C deposition and prevention of Ni particle sintering must be studied [13,[16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, Ni-based catalysts tend to become deactivated when subjected to long-term reactions due to C deposition and the sintering of Ni grains. erefore, resistance to C deposition and prevention of Ni particle sintering must be studied [13,[16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation procedure of 5%Co–2%Ce/ZrO 2 and 10%Co–2%Ce/ZrO 2 samples, the experimental setup, and equipment for feed and product analysis were used as described in our previous work . The physical properties of the catalysts such as crystallite sizes and surface areas were also detected and discussed previously …”
Section: Methodsmentioning
confidence: 99%
“…By using a similar approach for the Co–Ce/ZrO 2 system, properties of catalysts having different Co:Ce loading ratios and their CDRM performance characteristics were first obtained . The results revealed that both the properties and performances are highly sensitive to catalyst composition, i.e., the Co:Ce ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of carbon crystallinity can be justified using the relative integrated area of D-G bands (I D /I G ). A small I D /I G value demonstrates high crystallinity because of dominant amounts of graphitized carbon [30]. The 10% Co/Al 2 O 3 showed a lower graphitization extent (I D /I G = 2.20) than 3% Ce-10% Co/Al 2 O 3 (I D /I G = 1.63).…”
Section: Characterization Of Spent Catalystsmentioning
confidence: 96%